Pelaksanaan Membuka Dan Menutup Pelajaran Oleh Guru Kelas 1 Sekolah Dasar Semasa Pandemi Covid-19 : Indonesia - Wildan Nuril (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to see the success of learning in terms of how the teacher teaches and in terms of the stages of learning design that start with opening activities, core activities, and closing activities. Opening and closing lessons are basic teaching skills that need to be mastered by teachers to make learning effective by mentally preparing students and guiding students to have a summary of the material being studied. This research includes qualitative research using descriptive methods, data collection techniques used in the form of observation and reinforced by interviews and documentation studies. The results showed that grade I teachers had implemented opening and closing lessons by fulfilling existing components. The activity of opening and closing lessons is carried out by the teacher by adjusting the characteristics and abilities of class I students. The components of opening and closing lessons are carried out by the teacher, which has a good effect on the learning process that students follow.